Distribution and availability of raw materials for production of Nepali handmade paper from Daphne species in Darchula district, Nepal - Kharal, D. K.; Oli, B. N.; Poudel, I. (Banko Janakari, 2013)
The study, conducted in 2005 in Darchula district of the far western region of Nepal, aimed at assessing the distribution of Lokta plants (Daphne species) and the sustainable availability of their bark as a raw material for Nepali handmade paper. Stratifi ed random sampling design was adopted for collecting primary data from 340 circular shaped sample plots. The study revealed asymmetric distribution and production of Lokta in different Range post areas of Darchula district. While the tree diameter at 30 cm from base (D30) varied from 1 to 18 cm, the maximum tree height varied from 2.1 to 6 m. On the basis of diameter class, about 87 % of the bark weight was found to be of exploitable category. For the entire district of Darchula, the annual yield of Lokta bark for six years rotation amounted only to about two-third of the four years rotation. The study concludes that the stock of Lokta bark that prevails in the district can sustain promotion of Nepali paper production enterprises. DOI: http://dx.doi.org/10.3126/banko.v21i2.9126 Banko Janakari Vol. 21, NO. 2, 2011 Page: 24-30 Uploaded date: 10 November, 2013